Determinants of career advancement of academics in private institutions of higher learning in Malaysia - Arokiasamy, Lawrence; Ismail, Maimunah; Ahmad, Aminah; Othman, Jamilah (2011)
The dynamic changes in private higher education that were observed in Malaysia for the last 20 years have transformed the Malaysian educational scenario and have led to the immense expansion of educational institutions. The liberalization of the higher education in 1990s led to the rapid increase in the number of students in higher institutions. The increase in demand for higher education has resulted in the growing demand for private higher education in Malaysia. Therefore, studies on academic career advancement have become essential for higher education in the country besides becoming competitive. This article examines the factors influencing the career advancement of academics in the private institutions of higher learning (IHL). The research used a survey involving 212 academic staff in selected private IHLs. The individual and organizational factors were included in this study as the determining variables. Finally the implications of the study to Human Resource Development (HRD) are discussed.